PENGARUH STRATEGI PEMBELAJARAN SEPAK BOLA VERBAL TERHADAP AKTIVITAS BELAJAR PPKn SISWA KELAS VIII DI SMP NEGERI 14 PEKANBARU - Tommy, Muhammad; Gimin, Gimin; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was motivated by the low learning activities of PPKn students of class VIII in Pekanbaru State Middle School 14. The formulation of the research problem is "Is there influence on the use of Verbal Soccer learning strategies on the eighth grade students' PPKn learning activities in Pekanbaru State Middle School 14?". This study was to determine the effect of the use of Verbal Soccer learning strategies on the learning activities of PPKn students of class VIII in Pekanbaru State Middle School 14. This research was conducted at Pekanbaru State Middle School 14 in August to September 2018. This research is an experimental quantitative descriptive study, the population in this study is class VIII Pekanbaru State Middle School 14. The sample in this study was taken based on the "Random Sampling" technique. Where the class taken as a sample is class VIII 3 (experimental class) given the Verbal Football learning strategy, and class VIII 5 (control class) are students who are given the conventional method. Then the data analysis using the homogeneity test and the "t" test. Based on the results of the study, there is an influence of learning activities between students who use the Verbal Football learning strategy and conventional methods in Pekanbaru State Middle School 14 (t_ (count = 3.11)> t_ (table = 1.99)). Where there is an increase in the average learning activities of the experimental class PPKn from 81.44% to 81.98% and the average learning activity of the control class PPKn from 52.06% to 69.97%. . Thus the hypothesis which states that there is an influence on the use of Verbal Soccer learning strategies on the learning activities of PPKn students of class VIII in Pekanbaru State Middle School 14, is acceptable.Keywords: Verbal Football, Activity